2012
DOI: 10.1128/aac.00406-12
|View full text |Cite
|
Sign up to set email alerts
|

Malachite Green Interferes with Postantibiotic Recovery of Mycobacteria

Abstract: The genus Mycobacterium comprises slow-growing species with generation times ranging from hours to weeks. The protracted incubation time before colonies appear on solid culture medium can result in overgrowth by faster-growing microorganisms. To prevent contamination, the solid media used in laboratories and clinics for cultivation of mycobacteria contain the arylmethane compound malachite green, which has broad-spectrum antimicrobial activity. Malachite green has no impact on the plating efficiency of mycobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…In contrast to previous studies attributing the post-antibiotic effect to biological mechanisms (7, 8), we show here that it may be explained by chemical processes alone. Our modeling framework makes testable predictions regarding the strength of the post-antibiotic effect that may be used to design antibiotics that can be given less frequently.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies attributing the post-antibiotic effect to biological mechanisms (7, 8), we show here that it may be explained by chemical processes alone. Our modeling framework makes testable predictions regarding the strength of the post-antibiotic effect that may be used to design antibiotics that can be given less frequently.…”
Section: Discussioncontrasting
confidence: 99%
“…Predictions of optimal dosing intervals are complicated by the fact that for some bacteria/antibiotic combinations, bacterial growth remains suppressed after removal of the antibiotic. This ‘post-antibiotic effect’ is not easily predicted, and has generally been attributed to bacterial stress responses induced by exposure to antibiotics (7, 8). …”
Section: Introductionmentioning
confidence: 99%
“…Mtb viability was determined by using liquid cultures manipulated under experimentally identical conditions as filter-grown cultures used for metabolomic profiling, which we had demonstrated to be microbiologically similar (25). Colony forming units (CFU) were determined by plating on m7H9 with Bacto Agar because of the apparent toxicity of malachite green to ICL-deficient Mtb with supplements; 0.2% glycerol, 0.2% dextrose, 0.5 g/L BSA, and 0.085% NaCl (26).…”
Section: Metabolomics With Lc-ms Lc-ms-based Metabolomics Analysis Wmentioning
confidence: 99%
“…For example, activated charcoal may sequester a component in the agar or in the 7H11-OADC medium in which the agar is dissolved, and that component might otherwise synergize with certain test agents to kill M. tuberculosis during the postantibiotic recovery phase of a CFU-based assay. For example, malachite green, a common component in 7H11-based agar, can potentiate the postantibiotic effect of cell-wall-active drugs on mycobacteria ( 56 ); perhaps activated charcoal can neutralize this effect. We have observed that M. tuberculosis bacilli form smaller colonies on 7H11-OADC plates containing activated charcoal, which suggests that the activated charcoal may bind essential nutrients, albeit not to an extent that abrogates the ability to form colonies.…”
Section: Discussionmentioning
confidence: 99%